Pemanfaatan Recycling Asphalt untuk Lapisan AC-WC dengan Penambahan Material Bottom Ash pada Perkerasan Lentur: Utilization of Recycling Asphalt for AC-WC Layers with The Addition of Bottom Ash Material to Pavement - Pasayu, Deliansyah; Arliansyah, Joni; Kadarsa, Edi (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2023)
Increasing road construction by adding a thick layer of asphalt on flexible pavement can cause problems, where the more viscous the asphalt layer, the higher the road will be than the houses. In addition, limited natural resources and large-scale use can damage the environmental system and make raw materials increasingly scarce, and their prices continue to increase. This research aims to show that recycled asphalt and bottom ash materials can be reused for flexible pavements. Researchers used experimental methods in the laboratory by testing using the Marshall Test. The results of this study indicate that the asphalt resistance based on the compressive strength of the asphalt mixture of recycled materials and the combination of recycled materials and bottom ash of 10% and 15% so that the values of VMA, VFA, Stability, Meltability, and MQ values ​​obtained from the Marshall Test according to with the General Specifications of Highways of the Ministry of Public Works. It was obtained from the provisions of the physical and mechanical test results of Bottom Ash sourced from the Petra UK Road Materials Laboratory Research with the bottom ash parameter passing the sieve of 18.2%. From the results of all asphalt tests, it is known that the addition of bottom ash to asphalt recycling where the extracted material from recycled asphalt (recycled) both asphalt and the aggregate material itself cannot be reused for flexible pavement layers. This is because the condition of asphalt recycling is old, and the strength of the material itself is weak, so it cannot last long if it is reused.